2005
DOI: 10.2174/1573405052953083
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Specific Imaging Using Tc-99m and Ga-68 Labeled Radiopharmaceuticals

Abstract: Improvement of scintigraphic tumor imaging is extensively determined by the development of more tumor specific radiopharmaceuticals. Thus, to improve the differential diagnosis, prognosis, planning and monitoring of cancer treatment, several functional pharmaceuticals have been developed. Application of molecular targets for cancer imaging, therapy and prevention using generator-produced isotopes are the major focus of ongoing research projects. Radionuclide imaging modalities (positron emission tomography, PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Yang and colleagues [13][14][15] found that EC-DG, which has characteristics similar to those of glucosamine, can easily be transported into tumor cells and enters the glycolysis/tricarboxylic acid cycle. EC-DG is synthesized from glucosamine by insertion of a dicysteine group at the 2-amino position of the glucosamine molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Yang and colleagues [13][14][15] found that EC-DG, which has characteristics similar to those of glucosamine, can easily be transported into tumor cells and enters the glycolysis/tricarboxylic acid cycle. EC-DG is synthesized from glucosamine by insertion of a dicysteine group at the 2-amino position of the glucosamine molecule.…”
Section: Discussionmentioning
confidence: 99%
“…L,L-ethylenedicysteine (EC) is the most successful example of N 2 S 2 chelates [14,[17][18][19]. EC can be labeled with both 68 Ga and 99m Tc efficiently with high radiochemical purity and the preparation remains stable for several hours [20].…”
Section: Selection Of Bifunctional Chelators For Imagingmentioning
confidence: 99%
“…The agents that could provide therapeutic prediction are either labeled molecular biomarkers or radiolabeled drugs. For example, radiolabeled annexin, a biomarker for apoptosis, is useful to evaluate the baseline level of apoptosis, predict the efficacy of therapy based on the detection of treatment-related apoptosis and possibly predict disease progression and prognosis [6,20,24]. As another example, assessment of pancreatic beta cell activity by a radiolabeled sulfonylurea receptor agent could provide early diagnosis of pancreatic diseases and monitor drug treatment response on pancreatic beta cells.…”
Section: Radiopharmaceuticals In the Prediction Of Therapeutic Responsementioning
confidence: 99%
See 1 more Smart Citation
“…However, [ 18 F]FMISO ( 1 ) was not an optimal hypoxic imaging agent. Because of the partitioning mechanism, [ 18 F]FMISO ( 1 ) shows a reduced accumulation of radioactivity in hypoxic cells and slow clearance in normal cells that lead to low tumor-to-background (T/B) ratios [8, 15]. Thus, new imaging agents with faster pharmacokinetics for ensuring higher T/B ratios are required.…”
Section: Introductionmentioning
confidence: 99%